Treatment-seeking behavior for malaria among communities in Indonesia: A systematic review - Philothra, Biodya D.; Alona, Ivana; Situmorang, Elizabeth; Limbardon, Patrick; Salsalina, Viktris G. (Narra Sains Indonesia, 2023)
Indonesia stands as one of the nine malaria-endemic countries in Southeast Asia with a total of 443,530 cases in 2022. Eastern Indonesia is listed as an area with high malaria endemicity and the Indonesian government has set a target of eliminating malaria by 2030. From 2010 to 2014, the number of malaria cases decreased but stagnated until 2020 and have continued to increase. Stagnation may occur as a result of many non-medical treatment-seeking behaviors. The aim of this systematic review was to provide a summary and overview of malaria treatment-seeking behavior among communities in several regions in Indonesia. The searches were conducted through four databases (Cochrane, PubMed, Google Scholar, and ScienceDirect) using medical subject headings (MeSH)